Stability of a Rock Tunnel Passing through Talus-Like Formations: A Case Study in Southwestern China - Shaoqiang Zhang; Wenqiang Li; Jiashan Tan; Bokuan Li; Xiaochang Li; Shuaifeng Wang; Zixin Zhang (Advances in Civil Engineering)
Tayi tunnel is one of the component tunnels in the Jian-Ge-Yuan Highway Project located in Yunnan Province, southeast of China. It mainly passes through talus-like formations comprised of rock blocks of diverse sizes and weak interlayers with clayey soils with different fractions. Such a special composition leads to the loose and fractured structure of talus-like formations, which is highly sensitive to the excavation perturbation. Therefore, Tayi tunnel has become the controlled pot of the whole highway project as the construction speed has to be slowed down to reduce the deformation of surrounding talus-like rock mass. To better understand the tunnel-induced ground response and the interaction between the surrounding rock mass and tunnel lining, a comprehensive in situ monitoring program was set up. The in situ monitoring contents included the surrounding rock pressure on the primary lining, the primary lining deformation, and the stress of steel arches. Based on the monitoring data, the temporal and the long-term spatial characteristics of mechanical behavior of surrounding rock mass and lining structure due to the excavation process were analyzed and discussed. It is found that the excavation of lower benches released the surrounding rock pressure around upper benches, resulting in the decrease of the surrounding rock pressure on the primary lining and the stress of steel arches. In addition, the monitoring data revealed that the primary lining sustained bias pressure from the surrounding rock mass, which thereby caused unsymmetrical deformation of the primary lining, in accordance with the monitored displacement data. A dynamically adaptive support system was implemented to strengthen the bearing capacity of the lining system especially in the region of an extremely weak rock mass. After such treatment, the deformation of the primary lining has been well controlled and the construction speed has been considerably enhanced.